2019
DOI: 10.1136/bmjoq-2018-000589
|View full text |Cite
|
Sign up to set email alerts
|

Improving oral health through dental fluoride varnish application in a primary care paediatric practice

Abstract: Dental caries affect 97% of people during their lifetime. A total of 59% of children aged 12–19 will have at least one documented cavity. The American Academy of Pediatrics recommends fluoridated toothpaste to all children starting at tooth eruption, regardless of caries risk. Besides, fluoride varnish is recommended for all children every 3–6 months from tooth emergence until they have a permanent dental home. This project aimed to increase oral fluoride varnish application for children starting at 6 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…Pediatric nurse practitioners (PNPs) represent a significant portion of the primary care workforce serving children and are uniquely positioned to provide preventative dental care and ongoing surveillance during well-child visits. Despite recommendation since 2014 by the U. S. Preventative Services Task Force that fluoride varnish be applied during well-child visits (children after the first tooth eruption until 5 years of age), few primary care practices report performing this simple preventive measure that takes 1–2 minutes to apply (Sudhanthar et al, 2019; USPSTF, 2014) and has shown to be modestly profitable to the primary care practice (Sibley, 2018). Thus, institution-based PNP curricula need to provide adequate oral health care education to ensure knowledge and clinical skills to identify early childhood caries (ECCs) and provide behavioral counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric nurse practitioners (PNPs) represent a significant portion of the primary care workforce serving children and are uniquely positioned to provide preventative dental care and ongoing surveillance during well-child visits. Despite recommendation since 2014 by the U. S. Preventative Services Task Force that fluoride varnish be applied during well-child visits (children after the first tooth eruption until 5 years of age), few primary care practices report performing this simple preventive measure that takes 1–2 minutes to apply (Sudhanthar et al, 2019; USPSTF, 2014) and has shown to be modestly profitable to the primary care practice (Sibley, 2018). Thus, institution-based PNP curricula need to provide adequate oral health care education to ensure knowledge and clinical skills to identify early childhood caries (ECCs) and provide behavioral counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, the American Academy of Pediatrics has been enabling pediatricians and ancillary medical staff in identifying oral disease and providing caries preventive services. According to a recent university-affiliated clinic-based study, improvement in adherence was noted in application of fluoride varnish per guidelines without affecting the flow of patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Es posible adherirse a las pautas de barniz de fluoruro oral para todos los niños menores de 3 años en una práctica de atención primaria. 43 Sin embargo, es de destacar que las aplicaciones tópicas de 0,1 ml de barniz de fluoruro aumentaron significativamente la excreción de fluoruro. 44 A pesar de que el barniz de flúor ha mostrado un efecto anticaries modesto en los preescolares.…”
Section: Discussionunclassified